Study on the Genus Pisonia L. (Nyctaginaceae) in Andaman and Nicobar Islands, India - Debasmita Dutta Pramanick; G. G. Maiti; M. S. Mondal (Recent Progress in Plant and Soil Research Vol. 3, 2021)
In India, the family Nyctaginaceae Juss. is characterised by 6 genera and 14 species, with the genus Pisonia L. being the most important due to its woody, arborescent habit, differential leaf arrangement pattern, presence of unisexual, hermaphrodite, and polymorphic flowers in the same and or different plants, unique anthocarp characteristics, and distinct types of pollen grains. During the taxonomic revision of the Nyctaginaceae family in India, the first author focused on the genus Pisonia L., with a detailed account of infra-generic taxa.The current paper discusses the current status of pisonia L. species in the Andaman and Nicobar Islands, as well as their correct nomenclature, diagnostic characters, phenology, ecology, distribution, and uses. To aid in the identification of the species, a key has been provided. A proposal was suggested to conserve the members of the genus Pisonia with restricted distribution. The distinct woody habit in combination with unisexual flower and unique nature of anthocarp made the genus unique representative of the family Nyctaginaceae.